2007
DOI: 10.1002/path.2239
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution analysis of DNA copy number alterations and gene expression in renal clear cell carcinoma

Abstract: We analysed chromosomal copy number aberrations (CNAs) in renal cell carcinomas by array-based comparative genomic hybridization, using a genome-wide scanning array with 2304 BAC and PAC clones covering the whole human genome at a resolution of roughly 1.3 Mb. A total of 30 samples of renal cell carcinoma were analysed, including 26 cases of clear cell carcinoma (CCC) and four cases of chromophobe renal cell carcinoma (ChCC). In CCCs, gains of chromosomes 5q33.1-qter (58%), 7q11.22-q35 (35%) and 16p12.3-p13.12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 49 publications
15
60
0
Order By: Relevance
“…Loss of 4q was observed in 10-50% of RCCs examined previously by conventional and array comparative genomic hybridization (Moch et al, 1996;Jiang et al, 2000;Yoshimoto et al, 2007). Several additional studies of RCC have also indicated that the loss of 4q is associated with sarcomatoid transformation and high-grade tumors (Jiang et al, 1998;Yoshimoto et al, 2007). In Wilms' tumors, a 2.4-Mb minimal region of loss of heterozygosity has been detected at 4q24-q25 by 10K SNP array, which is a CXXC4 and progression of RCC T Kojima et al region that includes the CXXC4 gene (Yuan et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Loss of 4q was observed in 10-50% of RCCs examined previously by conventional and array comparative genomic hybridization (Moch et al, 1996;Jiang et al, 2000;Yoshimoto et al, 2007). Several additional studies of RCC have also indicated that the loss of 4q is associated with sarcomatoid transformation and high-grade tumors (Jiang et al, 1998;Yoshimoto et al, 2007). In Wilms' tumors, a 2.4-Mb minimal region of loss of heterozygosity has been detected at 4q24-q25 by 10K SNP array, which is a CXXC4 and progression of RCC T Kojima et al region that includes the CXXC4 gene (Yuan et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…Loss of 4q was observed in 10-50% of RCCs examined previously by conventional and array comparative genomic hybridization (Moch et al, 1996;Jiang et al, 2000;Yoshimoto et al, 2007). Several additional studies of RCC have also indicated that the loss of 4q is associated with sarcomatoid transformation and high-grade tumors (Jiang et al, 1998;Yoshimoto et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Using a panel of tumor-suppressive chromosome 14 MCH cell lines established in a previous study (1), a novel candidate TSG, cysteine-rich intestinal protein 2 (CRIP2), was identified and shown to induce tumor suppression in nasopharyngeal carcinoma (NPC). CRIP2 is located in the chromosome 14q32.3 region, which often shows high allelic loss in many cancers, including NPC (2, 3) and esophageal, renal, and colon carcinomas (4)(5)(6)(7). In fact, because of its location in a hot spot for chromosome truncation in tumor development, it was reported to be a candidate for leukemic translocation (8).…”
mentioning
confidence: 99%
“…Among the RCC histotypes, clear cell renal carcinoma (ccRCC) is the most frequent and aggressive subtype and is characterized by a specific pattern of chromosomal alterations (Yoshimoto et al, 2007) that represents a molecular fingerprint potentially useful for diagnostic and prognostic applications (Klatte et al, 2007). Nowadays, the standard clinical treatment comprises surgical resection followed by IFN-and/or IL2-based immunotherapy, although therapy toxicity still represents a major problem (Molina & Motzer, 2011).…”
Section: Introductionmentioning
confidence: 99%